Indigenous livestock as the backbone of African animal agriculture: The importance of adaptive attributes and potential for their exploitation - Rege, J.E.O. (South African Society of Animal Science, 1994)
This paper summarises the adaptive traits of indigenous livestock breeds, presents a case for their improvement and outlines possible utilization strategies. Though the adaptive attributes of indigenous breeds of other species recognised, the discussion concentrates mainly on cattle. The discussion focusses on livestock functions in traditional systems; adaptation issues such as tolerance to climatic stress, nutritional aspects of adaptation, adaptation related to water metabolism and parasite and disease tolerance; comparative productivity and utilization of indigenous animal genetic resources. It is argreed that it may not be possible to sufficiently improve some of the environments in which traditional livestock rearing is practised to allow introduction of specialised exotic breeds.